1990
DOI: 10.1093/ejo/12.1.38
|View full text |Cite
|
Sign up to set email alerts
|

A long-term study of 370 autotransplanted premolars. Part IV. Root development subsequent to transplantation

Abstract: The purpose of the present study was to analyse the extent of root development subsequent to transplantation in a material of 370 transplanted premolars. Before transplantation, the grafts were classified according to stage of root development (i.e. quarters of root length and constriction of the apical foramen) and length of tooth development (measured in mm from the cusp tip to the apical foramen). At radiographic controls the extent of root formation was registered. These figures were compared to the final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
169
0
18

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(218 citation statements)
references
References 0 publications
6
169
0
18
Order By: Relevance
“…Avoidance of trauma is also important for the success of the transplant. Otherwise, trauma will become an extra cause of impaired healing [30][31][32]. Success is defined as normal periapical healing, without any inflammatory pulpal changes or progressive root resorption [4].…”
Section: Discussionmentioning
confidence: 99%
“…Avoidance of trauma is also important for the success of the transplant. Otherwise, trauma will become an extra cause of impaired healing [30][31][32]. Success is defined as normal periapical healing, without any inflammatory pulpal changes or progressive root resorption [4].…”
Section: Discussionmentioning
confidence: 99%
“…Andreasen et al [14][15][16][17] reported survival rates of more than 90% in a comprehensive study, but only a few of their transplants had an observation period of more than 10 years. The most complications associated with autotransplantation are ankylosis and root resorption.…”
Section: Discussionmentioning
confidence: 99%
“…ODT'de dişlerin sağ kalım oranları yüksek olmasına rağmen rezorpsiyon ve ankiloz gibi bazı istenmeyen komplikasyonlar görülmektedir (30). İşlem sırasında oluşan periodontal ligamentte hasar, ototransplantasyon sonrası 4 haftadan, 8 haftaya kadar klinik veya radyografik olarak teşhis edilebilen kök rezorbsiyonuna neden olabilir.…”
Section: Travmatik Intrüzyonunclassified
“…İşlem sırasında oluşan periodontal ligamentte hasar, ototransplantasyon sonrası 4 haftadan, 8 haftaya kadar klinik veya radyografik olarak teşhis edilebilen kök rezorbsiyonuna neden olabilir. Kök gelişimi tamamlanmış böyle dişlere sonrasında uygulanan ortodontik tedavi, hem yüzeysel hem de iltihabi kök rezorpsiyonu meydana gelmesinde hafif bir artış ile sonuçlanmıştır (30 …”
Section: Travmatik Intrüzyonunclassified